Clinical implications from daily physiotherapy examination of 131 acute hamstring injuries and their association with running speed and rehabilitation progression. Issue 5 (30th October 2017) - Whiteley, Rod; van Dyk, Nicol; Wangensteen, Arnlaug; Hansen, Clint
Abstract : Aim: To investigate the association of daily clinical measures and the progression of rehabilitation and perceived running effort. Methods: A cohort of 131 athletes with an MRI-confirmed acute hamstring injury underwent a standardised criteria-based rehabilitation protocol. Descriptive and inferential statistics were used to investigate the association between daily clinical subjective and objective measures and both the progression of rehabilitation and perceived running effort. These measures included different strength, palpation, flexibility and functional tests. Inter-rater and intrarater reliability and minimal detectable change were established for the clinical measures of strength and flexibility by examining measures taken on consecutive days for the uninjured leg. Results: The progression of the daily measures was seen to be non-linear and varied according to the measure. Intra-rater reliability for the strength and flexibility measures were excellent (95% CI ≥0.85 for all measures). Strength (in the outer range position) and flexibility (in maximum hip flexion with active knee extension (MHFAKE) in supine) were best associated with rehabilitation progression and perceived running effort. Additionally, length of pain on palpation was usefully associated with rehabilitation progression. At lower perceived running effort there was a large variation in actual running speed. Conclusion: Daily physical measures of palpation pain, outer range strength, MHFAKE and reported pain during daily activity are useful to inform the progression of rehabilitation. Trial registration number: NCT01812564 and NCT02104258 .